Caractérisation génétique de l’effort reproducteur de l’huître creuse, Crassostrea gigas, dans le cadre des mortalités estivales de juvéniles : Approch QTL - Flahauw, Emilie (Université de La Rochelle, Ecole doctorale Gay Lussac, 2013)
The Pacific oyster, Crassostrea gigas, is a major aquacultured species whose production represents an economic interest at worldwide, european and french levels. However, this species undergoes summer mortalities recorded from the beginning of the 20th century and, since 2008, this phenomenon increased and threatens mainly juvenile oysters. Aquaculture production of oysters suffers consequences of mass mortalities, that’s why this phenomenon has been studied for many years. In France, the bacterium Vibrio splendidus and the Ostreid virus Herpes Virus 1 (OsHV-1) are often associated with mass mortality outbreaks of juveniles oysters and it was demonstrated that selected individuals for resistance to summer mortality were able to slow the increasing in viral load OsHV-1 in their tissues and then to decline it. These same individuals also present a lighter reproductive effort than individuals selected for their sensitivity to summer mortality. In this context, this study aimed to improve the knowledge of genetic architecture of reproduction of C. gigas by identifying some regions of the genome called QTLs (Quantitative Trait Loci) involved in reproductive effort and highlighting possible genetic relationships between reproduction and survival; QTLs involved in survival being already detected. To characterize the reproductive effort, it was necessary to develop a set of new tools. From a biological point of view, 21 F2 families were produced from lines selected for their contrasting response to summer mortality. From a molecular point of view, new SNPs (Single Nucleotide Polymorphism) were developed to increase density of the genetic map already available for C. gigas. On a technical point of view, Magnetic Resonance Imaging (MRI) allowed to observe the gametogenesis of 300 individuals of the same family F2 during eight sessions over two years while previous studies were limited to a one-time observation because of the conventional methods of observation of gametogenesis leading necessarily to the death of the ...